Effect on Map Based Learning Activities of the Development of Map Reading Skills among Students at the Secondary Level - Sukhvinder; Kamath, Asha KVD (JOURNAL OF INDIAN EDUCATION, 2014)
Social Science is one of the compulsory school subjects up to secondary level in India. Teachers use several instructional resources to help children construct knowledge. The classroom environment provides students with numerous opportunities to participate in instruction that incorporates a variety of formats and learning tools. Map is an indispensable tool in social science. However, if maps are to be used correctly by the students, it is necessary that they know how to read maps and interpret them, as maps have their own language. Several skills have been identified by people who worked in the area of maps and they have been consolidated by Wilson (1980). Unless these skills are developed in the students they will not be able to make complete use of the maps given in the textbook as well as to go beyond the textbook- the map related problems which they encounter in their daily lives. Therefore, the investigators wanted to find out to what extent the students of class X have acquired the map reading skills and if it is not acquired at satisfactory level, to organise some map based activities to develop those skills among the students. The objectives of the study were to find the status of acquisition of mapreading skills among the students of Class X; to find the effectiveness of map based activities in developing map-reading skills among the students; to compare the effectiveness of map-based activities on boys and girls in developing map-reading skills and to find the effectiveness of map-based activities in developing each of the selected map-reading skills among the students. It was a single group pre-test/post-test experimental design. The sample of the study was 27 students (Boys- 15 and Girls-12) of Class X following CBSE syllabus. Tools of the study consisted of pre-test, post-test and learning activities prepared by the investigators. The findings of the study were that there is significant difference between pre-test and post-test mean scores. Therefore, the map-based activities have been effective in developing map-reading skills among the students; there is significant difference between the mean scores of boys and girls on the development of map-reading skills. Boys have scored higher mean than girls and though the map based activities have been effective in developing all the six selected map-reading skills, it has been more effective in improving the skills of symbols, map scale, location and inference when compared with the rest of the skills i.e. direction and colour.